Transgene pyramiding in wheat: Combination of deoxynivalenol detoxification with inhibition of cell wall degrading enzymes to contrast Fusarium Head Blight and Crown Rot. (December 2021) - Mandalà, Giulia; Ceoloni, Carla; Busato, Isabella; Favaron, Francesco; Tundo, Silvio
Highlights: Combined presence of the HvUGT13248 for DON-detoxification and AcPMEI or PvPGIP2 pectinase inhibitors increases resistance toward FHB disease Resistance to FCR was not affected by the stacking of UGT-based DON detoxification and increased methyl esterification by inhibition of plant PMEs F. graminearum produces PME and PG activities on seedlings but AcPMEI and PvPGIP2 wheat expression does not increase FCR resistance Abstract: Fusarium Head Blight (FHB) and Crown Rot (FCR) are major diseases of wheat crops, causing extensive damages and mycotoxin contamination. In this work, we investigated the possibility to improve resistance to either or both diseases by combining different resistance mechanisms. To this aim, we stacked in the same wheat genotype transgenes controlling the DON-to-D3G conversion by specific UDP-glucosyltransferases (UGT) and the inhibition of cell wall degrading enzymes (CWDEs) by glycosidase inhibitors. We obtained: i) a durum wheat UGT+PMEI double-transgenic line constitutively expressing the HvUGT13248 and AcPMEI genes, coding for a barley UGT and a kiwi pectin methylesterase inhibitor, respectively; ii) a bread wheat UGT+PGIP line, expressing in floral tissues the HvUGT13248 gene and constitutively the PvPGIP2 gene, coding for a bean polygalacturonase inhibiting protein. We observed that both UGT+PMEI and UGT+PGIP plants exhibited increased resistance against Fusarium graminearum in FHB, further reducing by 10–20 % FHB symptoms as compared to the lines carrying the individual transgenes, and of up to 50 % as compared to wild-type plants. On the other hand, double-transgenic UGT+PMEI seedlings exhibited similar FCR symptoms as the UGT single transgenic line after infection with F. culmorum, indicating no contribution of the PMEI transgene to FCR resistance. This result is also supported by the inability of AcPMEI or PvPGIP2, constitutively expressed in durum wheat transgenic lines, to counteract F. graminearum in FCR. We also verified that F. graminearum produces PG and PME activity on infected wheat crown. We conclude that CWDEs inhibition combined with UGT-based DON detoxification contribute in an additive manner to limiting F. graminearum in FHB. Conversely, UGT-based DON detoxification is the only mechanism contributing to resistance observed against FCR. Indeed, the reinforcement of pectin does not enhance resistance against FCR.